Analysis of factors affecting rehabilitation of abandoned mines in South Africa: cases on asbestos projects - Meyerowitz, Reuben Benjamin (University of the Witwatersrand, Johannesburg, 2024)
Asbestos was once mined in South Africa using traditional methods. Unfortunately, the exploitation of asbestos severely impacted both workers and the surrounding communities. In 2008, the government stopped asbestos mining and designated the abandoned mines as Derelict and Ownerless (D&O) Mines. This was done to mitigate the serious health and safety risks associated with asbestos mining. The aim of the programme was also to address the negative environmental impacts caused by abandoned mines on local areas and social environments. Since 2009, the MINTEK’s D&O programme has rehabilitated 38 mines. However, the rehabilitation of these mines has been affected by various factors that have impacted the Derelict and Ownerless mining projects. This study aims to identify and understand the factors that affect abandoned mine projects in South Africa. The study also aims to provide a comprehensive analysis of the identified impacts and provide recommendations to ensure the successful implementation of the D&O projects. The study used a mixed-method approach to collect both quantitative and qualitative data. The methodology involved data collection from various sources such as recorded reports, financial statements, spreadsheets, engineer reports, project progress reports, construction programs, and document analysis. The study focused on 32 asbestos mining projects in four provinces, namely Northern Cape, Limpopo, KwaZulu Natal, and Mpumalanga, which were used as case studies. The rehabilitation of abandoned asbestos mines is a challenging task that requires collaboration, innovation, and concerted efforts. The factors affecting the implementation of the rehabilitation projects include slow decision-making by the contractors before and during construction, internal challenges faced by the contractors, time delays in material and stock deliveries, community resistance, specific project team experience, influence of external stakeholders and others. These can be categorized into six areas, namely, technical, economic, management, psychological, political and legislative. The study has revealed that all factors identified in the research have a direct impact on rehabilitation projects and contribute to failures in meeting targets in terms of costs and time. In conclusion, the analysis of technical, economic, psychological, and political factors in the rehabilitation of abandoned mines iv in South Africa also highlighted the interconnected nature of these considerations. As such, resolving these factors collectively will enhance the success and sustainability of mine rehabilitation projects. The recommendations from the study include improvements in contract management, ensuring project monitoring and evaluation that encompasses progress monitoring, data management and reporting, and the establishment of performance matrices. The other areas of intervention include policy and legal reforms to define the requirements and objectives of rehabilitation projects. Stakeholder engagement and capacity building are also key elements that have a major influence on the successful implementation of rehabilitation projects. By prioritizing factors and addressing these bottlenecks, the risks associated with asbestos rehabilitation can be mitigated to foster resilient and empowered communities that actively participate and benefit from the restoration processes.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Abandoned Mines; rehabilitation projects; project management; time and cost impacts; SDG-15: Life on land